2014
DOI: 10.1093/ehjci/jeu121
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical diastolic dysfunction in young adults with Type 2 diabetes mellitus: a multiparametric contrast-enhanced cardiovascular magnetic resonance pilot study assessing potential mechanisms

Abstract: In young adults with T2DM, diabetes duration and aortic distensibility were associated with diastolic dysfunction. Interventional studies are required to assess whether cardiac dysfunction can be reversed in this phenotype of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
81
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 63 publications
(88 citation statements)
references
References 37 publications
7
81
0
Order By: Relevance
“…1. A total of ten studies were included for the HCM group, 17,29-37 nine for DCM, 11,30,33,35,[38][39][40][41][42] twelve in MC, 30,[43][44][45][46][47][48][49][50][51][52][53] five in iron overload, 54-58 six in amyloidosis, 32,[59][60][61][62][63] two in Fabry disease, 64,65 ten in HT, 13,17,34,37,[66][67][68][69][70][71] four in DM, [72][73][74][75] and one in obesity 74 ( Table 1). The field strength is known to influence the T 1 values significantly 65 ; therefore, results from studies performed on a 1.5T or 3T are shown separately, but used as covariant in the meta-regression analysis.…”
Section: Results Of the Literature Searchmentioning
confidence: 99%
See 3 more Smart Citations
“…1. A total of ten studies were included for the HCM group, 17,29-37 nine for DCM, 11,30,33,35,[38][39][40][41][42] twelve in MC, 30,[43][44][45][46][47][48][49][50][51][52][53] five in iron overload, 54-58 six in amyloidosis, 32,[59][60][61][62][63] two in Fabry disease, 64,65 ten in HT, 13,17,34,37,[66][67][68][69][70][71] four in DM, [72][73][74][75] and one in obesity 74 ( Table 1). The field strength is known to influence the T 1 values significantly 65 ; therefore, results from studies performed on a 1.5T or 3T are shown separately, but used as covariant in the meta-regression analysis.…”
Section: Results Of the Literature Searchmentioning
confidence: 99%
“…Two studies reported clearly decreased T 1 values for DM, but had no healthy control population to compare them with. A reason for this decrease might be that DM patients are known to develop myocardial steatosis due to their insulin resistance, and the associated myocardial fat lowers the native T 1 value . However, the fat content of this myocardial steatosis is much smaller than in Fabry disease, and the number and size of T 1 mapping studies was too small to determine the influencing factors in this population.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Myocardial tissue tagging has traditionally been regarded as the reference method for the quantification of peak systolic strain [11, 12]. Feature Tracking (FT) is a novel post-processing strain quantification technique that can be performed on routinely acquired steady-state free precession cine sequences.…”
Section: Introductionmentioning
confidence: 99%